Специализированные системы электропитания для электротехнологического оборудования - Мартынов, В.В.; Руденко, Ю.В. (Технічна електродинаміка, 2012)
The features of power supply for power-full equipment are examined. It's shown that application of specialized power supplies which take the character of technological procedures into account allows to get over the conflicting demands to electro energy quality and technology processes effectiveness. The results of investigation of developed power supply systems with different purposes are given. Among them are the systems of power supply for electron-beam guns for welding and melting installations with power up to 500 kW , sources of bias voltage and generators of plasma for pvdtechnology with power up to 20 kW. These sources are equipped with high-efficiency protection from short circuits, have improved quality of transient processes and keep a substantially reduced energy store at the outputs.